Contrasting trait syndromes in angiosperms and conifers are associated with different responses of tree growth to temperature on a large scale - Carnicer, Jofre; Barbeta, Adria; Sperlich, Dominik; Coll, Marta; Penuelas, Josep (Frontiers in Plant Science, 2013)
Recent large-scale studies of tree growth in the Iberian Peninsula reported contrasting positive and negative effects of temperature in Mediterranean angiosperms and conifers. Here we review the different hypotheses that may explain these trends and propose that the observed contrasting responses of tree growth to temperature in this region could be associated with a continuum of trait differences between angiosperms and conifers. Angiosperm and conifer trees differ in the effects of phenology in their productivity, in their growth allometry, and in their sensitivity to competition. Moreover, angiosperms and conifers significantly differ in hydraulic safety margins, sensitivity of stomatal conductance to vapor-pressure deficit, xylem recovery capacity or the rate of carbon transfer. These differences could be explained by key features of the xylem such as non-structural carbohydrate content (NSC), wood parenchymal fraction or wood capacitance. We suggest that the reviewed trait differences define two contrasting ecophysiological strategies that may determine qualitatively different growth responses to increased temperature and drought. Improved reciprocal common garden experiments along altitudinal or latitudinal gradients would be key to quantify the relative importance of the different hypotheses reviewed. Finally, we show that warming impacts in this area occur in an ecological context characterized by the advance of forest succession and increased dominance of angiosperm trees over extensive areas. In this context, we examined the empirical relationships between the responses of tree growth to temperature and hydraulic safety margins in angiosperm and coniferous trees. Our findings suggest a future scenario in Mediterranean forests characterized by contrasting demographic responses in conifer and angiosperm trees to both temperature and forest succession, with increased dominance of angiosperm trees, and particularly negative impacts in pines.